O nosso rosto ainda é nosso? - Assis, Francisco Fagner Costa de (2024)
The expansion of facial recognition and deepfake technologies challenges the ownership of our own faces, raising profound ethical and legal questions. The central question of this study, "Is our face still ours?", resonates in an era where visual identity can be easily manipulated or falsified without the explicit consent of the individual. Addressing the complexities of interactions between technology and individual rights, this work investigates the implications of such technologies on personal control over one's own image. Facial recognition technologies, initially developed for security and service personalization, have evolved into tools capable of infringing individual privacy. The General Data Protection Law (LGPD) in Brazil represents an effort to protect personal data by requiring explicit consent for its use. However, market practices often subvert this protection, reducing an individual's autonomy over their own image through "take it or leave it" policies. The application of deepfakes, capable of transgressing copyright and personality rights, expands the scope of threats to privacy, dignity, and honor of individuals. These technologies challenge the notion of autonomy and control over one’s own image, creating convincing forgeries that can be used in various harmful contexts without permission. Although individuals can technically claim ownership of their images, the reality of technological advancements and data management practices often contradicts this notion. Ensuring control over one’s own face and visual identity requires robust legislation, rigorously applied consent practices, and increased public awareness. Effective protection of ownership over one's own face and the maintenance of personal autonomy in the face of facial recognition and deepfake technologies require ongoing efforts to adapt legislation and technology policies. Only then can we meet emerging challenges and ensure that visual identity remains under individual control in the future